EVALUASI TINGKAT KEBERHASILAN REVEGETASI TERHADAP PERTUMBUHAN DAN KESEHATAN TANAMAN PADA LAHAN BEKAS TAMBANG BATUBARA PT. AMANAH ANUGERAH ADI MULIA DI SITE RIAM ADUNGAN KABUPATEN TANAH LAUT - Azhar Azhar; Basir Achmad; Erwin Rosadi; Bambang Joko Priatmadi (EnviroScienteae, 2023)
Mining results in infertile soil, acidic pH and lack of nutrients. Reclamation activities are one way to restore the benefits of land to be better and more productive in solving this problem. Assessment of reclamation success has been carried out on 8 (eight) IUPs, one of which is PT. Amanah Anugerah Adi Mulia (PT. A3M) in Tanah Laut Regency, South Kalimantan Province. Status PT. A3M has entered the post-mining stage and has rehabilitated mining-affected areas through reclamation and revegetation on the inpit dump land which is divided into three areas, namely the AR-05 area of 3.26 ha of the 2011 Planting Year, the AR-07 area of 3.61 ha of the 2014 Planting Year and the AR-07 area of 3.27 ha of the 2017 Planting Year. Therefore, the purpose of this study is to analyze the status of revegetation success related to the growth and health of revegetated plants in PT. Amanah Anugerah Adi Mulia and identified the factors causing the non-success of revegetation related to the characteristics of post-mining revegetation land. The results of the revegetation analysis regarding the percentage of plant growth and health: the percentage of growth was 96% (2011), 100% (2014) and 100% (2017), with a success value of > 90% (successful category) and a percentage of plant health of 91.14% (2011), 99.2% (2014) and 89% (2017), with a plant health value of > 89% categorized as healthy (normal height, fresh leaves and not yellow).